Generation of Slot Index Tables for Time-Hopping Pseudolites with the Constructed Congruence Codes - Hu, Y.; Yu, B; Deng, Z; Yu, W (Společnost pro radioelektronické inženýrství, 2023)
The time-hopping (TH) pulsed pseudolite (PL) can be used to enhance the performance of global navigation satellite systems (GNSS), and the slot index table (SIT) is an important part to form this PL signal. In this paper, a new method to generate SITs for multiple PLs is proposed. The general process of the proposed method is that first different time-hopping slot index (THSI) base matrices are generated based on the constructed congruence codes, and then by combining several different THSI base matrices to constitute a new matrix, the SIT for a PL is formed. Further by changing the combined matrices, different SITs for different PLs can be generated. During this process, two critical factors that affect the performance of the given method, i.e., the collision or hit property of the generated THSI base matrix and the correlation property of the formed SIT, are analyzed in detail. The simulations given at the end of this paper show that compared with many other similar schemes, the SITs given by the proposed method can obtain better correlation performance and detection performance in the receiver, and these results also imply that the proposed method offers a more effective way to design this kind of PL signal.
Keywords: Global Navigation Satellite Systems (GNSS); time-hopping pseudolite; slot index table (SIT); congruence codes